Determination of soil erosion factors using universal soil loss equation and geographic information system in Ipoh City in Perak State, Malaysia - Mohamed Tekhikh Abdalfettah Addukali (2020)
Soil erosion is among of the most acute issues faced in the world, from the loss of soil to natural resources and crop farmers. Malaysia is a tropical country with high yearly rainfall affecting the loss of the outermost layers of soil. The main objectives of this study was to examine the areas mandatory for the evaluation of soil corrosion in Ipoh city and surrounding areas in Perak state, Malaysia for Year 2000 and Year 2015, and to evaluate the mean yearly soil loss proportion using the USLE model. The total area covered in this study was 1267.83 km2. Results showed that the proportion of agriculture land in the study area increased significantly from 2000 to 2015 (30% to 34.35% of the total study area, respectively). Similarly, urban area also showed increase from 14.34% in 2000 to 17.93% in 2015 with values of 183.1 km2 to 216.16 km2of study area, respectively. Contrary, open area showed significant reduction in size from 118.76 km2 (8.30% of the study area) in 2000 to 48.80 km2 (3.82% of the study area) in 2015. Forest area also decreased from 45.1% in 2000 to 42.5% in 2015. These reductions resulted to an overall decrease in total areas with very low probability of soil erosion from 90.96% in 2000 to 76.42% in 2015. On the other side of the spectrum, the areas with very high probability of soil erosion increased from 36.78 km2 of the study area in 2000 to 94.85 km2 in 2015, showing 4.58% increase. In conclusion, decrease in forest and open areas significantly contributed to increase in agriculture and urban areas with higher soil erosion probability. Urban planners and land developers exploited the potential land at maximum rate by building residential, commercial and industrial areas. Even though the soil erosion rate in the study area was found not to be at a pressing stage, it can increase in the future if the development activities are done without conservation planning program in the Ipoh city and surrounding areas in Perak state.